European yearbook of minority issues volume 8, 2009 - European Centre for Minority Issues (Leiden Martinus Nijhoff Publishers, 2011)
The European Yearbook of Minority Issues provides a critical and timely review of contemporary developments in minority-majority relations in Europe. It combines analysis, commentary and documentation in relation to conflict management, international legal developments and domestic legislation affecting minorities in Europe.
Published: Leiden : Nijhoff, 2004-
CSSP-7991 donated by Brill Publsihers through SPi Global Foundation, Inc.
Keywords: Minorities -- Legal status, laws, etc. -- Europe -- Periodicals; Minorities -- Civil rights -- Europe -- Periodicals; Europe -- Ethnic relations -- Periodicals